2020
DOI: 10.1101/2020.07.22.20160291
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The collective wisdom in the COVID-19 research: comparison and synthesis of epidemiological parameter estimates in preprints and peer-reviewed articles

Abstract: Background Research papers related to COVID-19 have exploded. We aimed to explore the academic value of preprints through comparing with peer-reviewed publications, and synthesize the parameter estimates of the two kinds of literature. Method We collected papers regarding the estimation of four key epidemiological parameters of the COVID-19 in China: the basic reproduction number (R0), incubation period, infectious period, and case-fatality-rate (CFR). PubMed, Google Scholar, medRxiv, bioRxiv, arRxiv, and SSRN… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 21 publications
2
3
0
Order By: Relevance
“…The semantic analysis of the title, abstract, and body of the preprints in arXiv and bioRxiv found little notable difference with their peer-reviewed versions (44). Comparison of preprints and their peer-reviewed versions on COVID-related research also found coherence in the reported results (41, 44, 46), extending the findings of these studies. In addition, analysis of the primary data constituting the evidence base suggests that estimate values in published papers are nearly identical to those in preprint versions (24, 25).…”
Section: Discussionsupporting
confidence: 76%
“…The semantic analysis of the title, abstract, and body of the preprints in arXiv and bioRxiv found little notable difference with their peer-reviewed versions (44). Comparison of preprints and their peer-reviewed versions on COVID-related research also found coherence in the reported results (41, 44, 46), extending the findings of these studies. In addition, analysis of the primary data constituting the evidence base suggests that estimate values in published papers are nearly identical to those in preprint versions (24, 25).…”
Section: Discussionsupporting
confidence: 76%
“…Third, for both high-and low-quality preprints, the checklist highlighted issues with transparency and research integrity. This mirrors the state of the COVID-19 literature, as we have seen that though the credibility of the research reported in preprints can be sound (32)(33)(34), data and materials sharing may nonetheless often be lacking (18,19). This could be taken as a weakness of the checklist, as this item is not particularly discriminative of preprint quality.…”
Section: Discussionsupporting
confidence: 57%
“…Preprints on clinical trials for example were shown to report results that may be just as credible as those of publications (32). This finding is reinforced by comparisons between preprints and publications on metrics like the basic reproduction number, transmissibility, incubation period, and infectious period, showing no evidence for a difference in the results presented in peer-reviewed vs. non-peer-reviewed literature (33,34). Nonetheless, a large portion of COVID-19 preprints show substantial changes in methods and results after peer-review (nearly half of the preprints analysed by Oikonomidi (2020) and Nicolalde et al (2020) (25,27)), suggesting flaws in the most essential elements of many COVID-19 preprints.…”
Section: Constructing and Validating Precheck: A Checklist To Evaluat...mentioning
confidence: 99%
“…Studies suggest that the discrepancy between the preprints and peer-reviewed articles is minor and the quality of reporting is within comparable range, advocating in favor of sharing research findings in preprints (19, 21). Wang et al also compared epidemiological estimates for preprints and published articles (separate articles, rather than different versions of the same papers as studied here), and found that basic reproduction number, incubation period, and infectious period were similar in preprints and peer-reviewed articles (24).…”
Section: Discussionmentioning
confidence: 89%
“…As discoveries are posted to preprint servers, disclaimers have been added to emphasize that the paper has not been peer reviewed (16). However, as noted above, little is known about how the extent to which data in biomedical preprints systematically differ from their peer-reviewed counterfactuals, despite the importance of this emerging question (17)(18)(19)(20)(21)(22)(23)(24). This knowledge gap is concerning not only for navigating preprints in this infectious disease outbreak, but also for navigating future emergencies.…”
Section: Introductionmentioning
confidence: 99%